2008
DOI: 10.21608/jpp.2008.170393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training System and Fruiting Unit Length on Bud Behaviour, Growth and Productivity of Flame Seedless Grapevines

Abstract: This investigation was conducted for two successive seasons (2006& 2007) to study the effect of training system and fruiting unit length on bud behaviour, growth and productivity of Flame Seedless grapevines. The chosen vines were ten-year-old, grown in a clay loamy soil and irrigated by the drip irrigation system. The vineyard was located at Meniet Samannoud, Dakahlia governorate. Vines were spaced at 2.5 X 3 meters apart, pruned during the second week of February with a load of (40-42 buds/vine) and trellis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…They revealed that the percentage of bud burst was negatively correlated with the number of buds left after pruning. Moreover, Abbas et al (2008) and Abo-Elwafa (2018) showed that the percentage of bud burst increased with decreasing spur length.Coefficient of bud fertility…”
Section: Percentage Of Bud Burstmentioning
confidence: 96%
See 4 more Smart Citations
“…They revealed that the percentage of bud burst was negatively correlated with the number of buds left after pruning. Moreover, Abbas et al (2008) and Abo-Elwafa (2018) showed that the percentage of bud burst increased with decreasing spur length.Coefficient of bud fertility…”
Section: Percentage Of Bud Burstmentioning
confidence: 96%
“…They found that bunch weight and dimensions were reduced by increasing bud load. Moreover, Abbas et al (2008) and Abo-Elwafa (2018) showed that bunch weight and dimensions increased with decreasing spur length.…”
Section: Physical Characteristics Of the Bunchmentioning
confidence: 98%
See 3 more Smart Citations